2023
DOI: 10.1162/jocn_a_01945
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric Asymmetries of Individual Differences in Functional Connectivity

Abstract: Resting-state fMRI studies have revealed that individuals exhibit stable, functionally meaningful divergences in large-scale network organization. The locations with strongest deviations (called network “variants”) have a characteristic spatial distribution, with qualitative evidence from prior reports suggesting that this distribution differs across hemispheres. Hemispheric asymmetries can inform us on constraints guiding the development of these idiosyncratic regions. Here, we used data from the Human Connec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 130 publications
1
8
0
Order By: Relevance
“…Furthermore, we examined potential relationships between networks’ NSAR values and found evidence supporting a dependent hypothesis of lateralization. These findings shed new light on hemispheric specialization, which has implications for the understanding of brain organization and development (Toga & Thompson, 2003), individual differences (Perez et al, 2023), human-defining cognitive processes (Hartwigsen et al, 2021), and neurodevelopmental conditions (Eyler et al, 2012; Kong et al, 2022). Previously, functional lateralization has been assessed through a variety of approaches dependent on intrinsic connectivity, primarily at the group level.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Furthermore, we examined potential relationships between networks’ NSAR values and found evidence supporting a dependent hypothesis of lateralization. These findings shed new light on hemispheric specialization, which has implications for the understanding of brain organization and development (Toga & Thompson, 2003), individual differences (Perez et al, 2023), human-defining cognitive processes (Hartwigsen et al, 2021), and neurodevelopmental conditions (Eyler et al, 2012; Kong et al, 2022). Previously, functional lateralization has been assessed through a variety of approaches dependent on intrinsic connectivity, primarily at the group level.…”
Section: Discussionmentioning
confidence: 94%
“…This was the case for the Dorsal Attention-B network, which was not a significantly lateralized network across the three datasets. However, there is evidence for a left-lateralized dorsal attention network across both left-and right-handed individuals, stemming from a within-individual network variants approach (see Figure 7 Panel C of Perez et al, 2023). Additionally, it could be that a finer-grained parcellation deconstructs the dorsal attention network into one bilateral and one lateralized network, similar to previous within-individual work on the default network (Braga & Buckner, 2017; DiNicola et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our analysis, we were only able to detect activity in left prefrontal areas. Several studies have reported on asymmetries within the FP network in the sense that left and right FP networks have different patterns in timing and are related to distinct processes in cognitive control (Budisavljevic et al, 2017; Ogawa et al, 2022; Perez et al, 2022). There is a possibility that activation in the left FP network serves distinct functions such as rule and stimulus processing, target evaluation, and the decision making process itself rather than response evaluation and adjustment, which might be performed by the right FP network (Gold & Shadlen, 2007; Gratton et al, 2017).…”
Section: Discussionmentioning
confidence: 99%